Myxoid degeneration of leiomyoma-a masquerader - Panda, Anuradha; Mahoorkar, Deepti N.; Reddy, Nikitha; Reddy, B. Mounika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine leiomyomas are one of the most common benign lesions in the uterus. The lesion can vary in size from a few millimetres to centimetres, location, its presentation and degeneration. They are easy to diagnose clinically with the help of available imaging techniques. Myxoid degeneration is an uncommon degeneration and has to be kept as a differential diagnosis as it mimics uterine sarcoma. Histopathology and Immunohistochemical analysis help in confirming the diagnosis. Here is a patient in reproductive age group who presented with rapidly growing abdominal mass in a span of 1 year with a prior surgical history of myomectomy. Pre-operative imaging was inconclusive for benign etiology and possibility of uterine leiomyosarcoma could not be ruled out. She was hence counselled for a laparotomy with a frozen section to prevent extensive surgery. Myxoid degeneration is not a common degeneration of leiomyoma with a reported incidence of 10% while the incidence of uterine leiomyosarcoma is less than 1% in reproductive age group. Even though rare, myxoid degeneration should be considered as a differential diagnosis of rapidly growing uterine mass with inconclusive pre-operative imaging.